2018
DOI: 10.1016/j.preghy.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk of eclampsia or HELLP-syndrome by institution availability and place of delivery – A population-based cohort study

Abstract: Background: Obstetric care in midwife-led institutions may be more cost-effective and reduce the number of interventions during labour. On the other hand, large obstetric institutions may offer more technologically advanced and specialised care. Knowledge of how availability of and access to different types of obstetric institutions impact maternal and perinatal clinical outcomes in a high-income context is lacking. Aims: The aim of this thesis was to assess availability of and access to obstetric institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 69 publications
(74 reference statements)
0
14
0
2
Order By: Relevance
“…These findings indicate that women with a known high‐risk pregnancy receive adequate care. However, another Norwegian study found a 50% increased risk of eclampsia/HEELP in nulliparous women living more than 1 hr away from the hospital, underlining how reduced availability may delay or complicate the identification of obstetric emergencies (Engjom et al, ). One Australian study examining the details in 4,096 maternity‐related cases reports various obstetric complications in relation to out‐of‐hospital care, such as postpartum haemorrhage, breech position, cord prolapse, prematurity and neonatal death (McLelland et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicate that women with a known high‐risk pregnancy receive adequate care. However, another Norwegian study found a 50% increased risk of eclampsia/HEELP in nulliparous women living more than 1 hr away from the hospital, underlining how reduced availability may delay or complicate the identification of obstetric emergencies (Engjom et al, ). One Australian study examining the details in 4,096 maternity‐related cases reports various obstetric complications in relation to out‐of‐hospital care, such as postpartum haemorrhage, breech position, cord prolapse, prematurity and neonatal death (McLelland et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…One Australian study reported that 11% of women attended by EMTs during labour gave birth before arriving at hospital; of these, 27% were recorded with antenatal and/or intrapartum complications, while 22% of the babies were recorded with an Apgar score lower than 7 (Flanagan, Lord, & Barnes, ). Risk factors associated with both maternal and neonatal outcomes in unplanned out‐of‐hospital births include maternal characteristics (young maternal age, low socio‐economic status, immigrant background, smoking), pregnancy‐related factors (multiparity, placental conditions, low birthweight, prematurity, infections, concealed pregnancy) and poor antenatal care (Boland et al, ; Engjom, Morken, Høydahl, Norheim, & Klungsøyr, ; Gunnarsson, Fasting, Skogvoll, Smárason, & Salvesen, ; Jones et al, ; Nguyen et al, ; Unterscheider et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…As such, transportation is emphasized as essential to achieve timely care [62][63][64][65][66]. Availability of resources includes availability of expertise, facility, technology, diagnostics and therapy [67][68][69][70][71][72][73][74]. For example, Hein & Burmeister [75] explained PLOS ONE that risk selection enables care providers to anticipate the limitations of their own facilities, and Smit and colleagues [72], studied whether access to pulse oximetry for the assessment of infants born in a community based midwifery care setting could prevent referral to a paediatrician.…”
Section: Risk Selection As An Organisational Measure: Aligning Risk Amentioning
confidence: 99%
“…An increased incidence in Latin American countries was previously reported and related to several factors like socioeconomic status, country developments and improvement in diagnosis [4,5]. Late care-seeking behavior and diagnosis and management delay are important risk factors for increased morbidity and mortality among women with preeclampsia [6]. A recent study found that nulliparous women living more than 1 h from obstetric units have a 50% increased risk of eclampsia [6].…”
Section: Introductionmentioning
confidence: 96%